Mini Invasive Floating Metatarsal Osteotomy for Diabetic Foot Ulcers Under the First Metatarsal Head: A Case Series. (June 2022) - Tamir, Eran; Smorgick, Yossi; Ron, Guy Zvi; Gilat, Ron; Agar, Gabriel; Finestone, Aharon S.
Diabetic foot ulcers under the first metatarsal head are difficult to treat and prevent recurrence. The aim of this study is to summarize the results of a distal first metatarsal minimally invasive floating osteotomy for ulcers under the first metatarsal head in patients with diabetic neuropathy. We reviewed files of patients with diabetic neuropathy undergoing a floating first metatarsal osteotomy. Demographic and clinical data were collected and analyzed to determine success and complications. We found records for 21 patients (mean age 64) with University of Texas 1A ulcers. The ulcer's mean age was 11.2 months. Following surgery, the ulcer completely resolved after a mean of 3.7 (2 to 11) weeks in 19 patients. During the first year, there were 4 complications related to the surgery (including 3 infections). At latest follow-up, 17/21 (81%) patients had healed with satisfactory results. Minimal invasive floating distal osteotomy of the first metatarsal can cure and prevent recurrence of diabetic foot ulcers under the first metatarsal head in 80% of the patients, but the ability to provide close follow-up and prompt response are prerequisites.